1999
DOI: 10.1021/bi9815905
|View full text |Cite
|
Sign up to set email alerts
|

The Cytosolic Class II Chaperonin CCT Recognizes Delineated Hydrophobic Sequences in Its Target Proteins

Abstract: The nonhomologous proteins actin and alpha- and beta-tubulin need the assistance of the cytosolic chaperonin containing TCP-1 (CCT) to reach their correct native state, and their folding requires a transient binary complex formation with CCT. We show that separate or combined deletion of three delineated hydrophobic sequences in actin disturbs the interaction with CCT. These sites are situated between residues 125-179, 244-285, and 340-375. Also, alpha- and beta-tubulin contain at least one recognition region,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
81
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 55 publications
6
81
0
Order By: Relevance
“…Thus, like the situation in vitro, at least some pVHL interacts with CCT in vivo. Some polypeptides that fold via a CCT-mediated pathway (e.g., tubulins and actins) contain particular subdomains that display an affinity for CCT (6,19,49,50). Relevant to the present study, a 55-amino-acid region (residues 100 to 155) of pVHL has been shown to be necessary and sufficient for binding to CCT (9).…”
Section: Resultssupporting
confidence: 56%
“…Thus, like the situation in vitro, at least some pVHL interacts with CCT in vivo. Some polypeptides that fold via a CCT-mediated pathway (e.g., tubulins and actins) contain particular subdomains that display an affinity for CCT (6,19,49,50). Relevant to the present study, a 55-amino-acid region (residues 100 to 155) of pVHL has been shown to be necessary and sufficient for binding to CCT (9).…”
Section: Resultssupporting
confidence: 56%
“…However, the search for TRiC-recognition determinants in substrate proteins has yielded conflicting data. Studies using actin indicate several possibilities, ranging from polar and charged sequences surface-exposed on the native protein [33] to delineated, hydrophobic sequences [34]. Recognition of native, surface-exposed, charged elements is novel for a molecular chaperone and raises questions of how binding interactions might be disrupted permanently to release the folded substrate and how TRiC might discriminate between native and non-native states.…”
Section: Tric-substrate Interactionsmentioning
confidence: 99%
“…However, no sequence homology between the p4 and p6 proteins can be seen except for their unusually high proline content. The core TRiC binding domain of ␤-tubulin was defined through mutagenesis and proteolytic analyses; it spans amino acids 150 to 350 and contains many proline and hydrophobic residues (6,40). There are no conserved sequences among the core domains of ␤-tubulin, VHL (10), and ␤-actin (20).…”
Section: Vol 75 2001mentioning
confidence: 99%